(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is dedicated to the novels written in the years of Independence; they are grouped due to their themes. The novels of the contemporary period are investigated in terms of the idea and content. The comparative analysis of the popular themes of the historical novels is based on a particular novel. The paper deeply deals with novels on historical themes. The Kazakh historical novels originating from the creativity of I. Esenberlin were far ahead both in their quality and quantity in the last quarter of the twentieth century; it is also typical for the first decade of Independence. That is the reason why the authors dwell on the kinds of historical novels, which take up the idea of independence, national idea, as well as other historical themes. Novels are identified by the clarification of the phenomenon of historicity. The attention is paid to the writer’s skills and the beauty of the work. The life of characters of the novels, revolution, famine, war, the ideological content and artistic solutions concerning the December events of 1986 called Zheltoksan are analyzed in the article.